Budaya Malu Sebagai Fakta Sosial Pemberantasan Korupsi di Indonesia - Syifa Najla Widiyanti; Kamaruddin Salim (Ilmu dan Budaya, 2023)
The culture of shame as a social fact in eradicating corruption in Indonesia. The culture of shame is able to prevent individuals and community groups from corrupt practices. Emile Durkheim's social facts describe that shame can prevent individuals from committing social deviance. This study used a qualitative method by conducting a literature review through journals, books, related publications and news articles which were then examined from the perspective of Emile Durkheim's social fact theory. The results of this study, a culture of shame is a solution to eradicating corruption. The government should make a new policy related to eradicating corruption. First, replace the term corruptor with the word thief or robber; secondly, corruptors are required to work without pay in the border areas that have been determined by the government as a substitute for imprisonment; third, violation of access of corruptors from all forms of public services, for example banking arrangements, passports, insurance, bank guarantees etc.; fourth, every candidate for public leader, is committed to anti-corruption by agreeing to a stamped agreement. If you commit a criminal act of corruption, you must return your salary while serving as an official or leader of a government agency.Budaya malu sebagai fakta sosial dalam pemberantasan korupsi di Indonesia. Budaya malu mampu menghindari individu maupun kelompok masyarakat dari praktik korupsi. Fakta sosial Emile Durkheim menggambarkan rasa malu dapat menghindari individu untuk melakukan penyimpangan sosial. Penelitian   ini, menggunakan metode kualitatif dengan melakukan studi pustaka melalui jurnal, buku, publikasi lembaga terkait dan artikel berita yang kemudian dikaji dalam perspektif teori fakta sosial Emile Durkheim. Hasil dari penelitian ini, budaya malu menjadi solusi pemberantasan korupsi. Pemerintah seharusnya membuat kebijakan baru terkait pemberantasan korupsi. Pertama, menggantikan istilah koruptor dengan kata maling atau garong; kedua, pelaku korupsi diwajibkan bekerja tanpa upah di wilayah perbatasan yang telah ditentukan oleh pemerintah sebagai pengganti hukuman penjara; ketiga, pembatasan akses pelaku korupsi dari segala bentuk pelayanan publik, misalnya pengurusan perbankan, paspor, asuransi, pinjaman bank dll; keempat, setiap calon pemimpin publik, berkomitmen terhadap anti rasuah dengan menandatangani surat perjanjian bermaterai. Apabila melakukan tindak pidana korupsi, maka harus mengembalikan gaji selama menjadi pejabat atau pemimpin suatu institusi pemerintah.